An algebra problem by Satwik Murarka

Algebra Level 2

f ( x ) = x 9 6 x 8 2 x 7 + 12 x 6 + x 4 7 x 3 + 6 x 2 + x 3 f(x)=x^{9}-6x^{8}-2x^{7}+12x^{6}+x^{4}-7x^{3}+6x^{2}+x-3

Find f ( 6 ) f(6) .


Source: IIT-JEE 1979


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Satwik Murarka
Apr 6, 2017

Solution:

f ( x ) = x 9 6 x 8 2 x 7 + 12 x 6 + x 4 7 x 3 + 6 x 2 + x 3 f ( 6 ) = [ 6 9 6 ( 6 8 ) ] + [ 2 ( 6 7 ) + 12 ( 6 6 ) ] + [ 6 4 7 ( 6 3 ) + 6 ( 6 2 ) ] + 6 3 f ( 6 ) = ( 6 9 6 9 ) + ( 12 ( 6 6 ) + 12 ( 6 6 ) ) + ( 6 4 + 6 3 7 ( 6 3 ) ) + 6 3 f ( 6 ) = 6 3 = 3 \begin{aligned}f(x)& =x^{9}-6x^{8}-2x^{7}+12x^{6}+x^{4}-7x^{3}+6x^{2}+x-3\\ f(6)& =[6^{9}-6(6^{8})]+[-2(6^{7})+12(6^{6})]+[6^4-7(6^{3})+6(6^{2})]+6-3\\ f(6) & = \cancel{\color{#3D99F6}(6^{9}-6^{9})}+ \cancel{\color{#D61F06}(-12(6^{6})+12(6^{6}))}+\cancel{\color{#20A900}(6^{4}+6^{3}-7(6^{3}))}+6-3 \\f(6)&=6-3=\boxed{3}\end{aligned}

It is the standard in Brilliant.org that we don't enter text in LaTex. I have edited the problem and solution for you. When using align enter an "&" before "=" so that each line is align at "&" as "\begin{align} f(x) & = ... \end{align}". It is better to leave spaces for ease of editing. You need to enter \require{cancel} before you can use \cancel.

Chew-Seong Cheong - 4 years, 2 months ago

@Chew-Seong Cheong - Thank you Sir for your assistance.I am still learning and will keep in mind the points you mentioned.

Satwik Murarka - 4 years, 2 months ago
Roger Erisman
Apr 7, 2017

Use synthetic division:

6| 1 -6 -2 12 0 1 -7 6 1 -3

  _6_0_-12_0_0_6_-6_0_6_

 1 0-2 0 0 1 -1 0 1 3

Remainder = 3 so f(6) = 3

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...